PRODUCT MARKET EXPANSION STRATEGY FOR BUSINESS DEVELOPMENT OF THE COMPANIES OPERATING IN THE FIELD OF PREMISES CLEANING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The long-term strategic development of cleaning companies cannot be implemented by providing only one type of service - cleaning of premises.Within this research the author studied the theoretical aspects of corporate strategies, product market expansion strategy for business development of the cleaning companies, to understand the industry of cleaning of premises and challenges of that industry.A monographic and descriptive method was used to analyze the theoretical aspects of company strategies, secondary data analysis and expert interview were used to describe the situation of premises cleaning industry, but quantitative research method such as analyzing of statistical data of the cleaning of premises companies, in connection with the comparative, analytical, deductive, logical approach method was used in this research.The research identifies factors that the expansion of the range of services is relevant in every business and every industry, because every industry develops over time, new regulations are adopted that can affect the respective industry, which means that companies are constantly forced to adapt to changing business, economic and political conditions.The research finds that if the company has successfully developed, has found its market share, and is working with good results, this does not mean that the company can relax and not think about its development.